Isolation of a CEL 1 Homolog in tomato (Solanum lycopersicum L.) fruit as a cost-effective endonuclease source for targeting induced local lesions in the genome (TILLING) analysis - Alcasid, Rochelle E. (Philippine Journal of Science, 2019)
CEL 1, an endonuclease originally purified from celery, has been used in TILLING (Targeting Induced Local Lesions IN the Genome) analysis to cut the hairpin loop and single-strand DNA generated from heteroduplex of mutant and wild DNA molecules. However, one major limitation as with most mutation screening technologies and especially in a large-scale application is the availability of affordable sources of endonuclease. This study searched for CEL 1 gene homologs in tomato through Basic Local Alignment Search Tool for nucleotides (BLASTn) and relevant bioinformatics analysis in public genomic databases. Results showed that the SlENDO 1 gene (SGN Accession Number Solyc02g078910.1.1) of tomato (Solanum lycopersicum) has the highest homology of 78% to CEL 1 among all the Solanum species. As annotated, the SlENDO 1 gene has a genome sequence length of 2.182 Kb and consisting of eight and nine intron-exon sequences, respectively. For molecular confirmation, polymerase chain reaction (PCR) primers were designed to target the conserved gene region of SlENDO 1. The amplification and specificity of these primers were further verified first by in silico PCR prior to synthesis. The designed SlENDO 1-specific DNA marker has successfully amplified the target gene in five tomato varieties in actual wet-laboratory PCR experiments. Interestingly, the designed marker was able to cross-amplify orthologous regions (candidate regions of nuclease PA3, TIGR LOC_Os04g54390) in Nipponbare and IR64 rice varieties. Once validated using a wide-range of crop species, the developed SlENDO 1-specific DNA marker can be potentially used in rapid detection of gene homologs in other plants. The isolation of the SlENDO 1 enzyme was also done using a modified protocol for CEL 1 isolation in celery. Through preliminary EcoTILLING with rice positive control samples, the purified SlENDO 1 from unripe fruits of non-transgenic tomato was confirmed to have the same mutation cleavage specificity as that of the CEL 1 endonuclease. Unlike celery, tomato fruits are readily available in any vegetable market, shop, or store in the Philippines. Likewise, they can easily be grown in greenhouse and field production.